Crustacea (Anomura, Brachyura) from the Miocene of Veracruz and Chiapas, Mexico: New records and new species. (June 2020) - Luque, Javier; Nyborg, Torrey; Alvarado-Ortega, Jesús; Vega, Francisco J.
Abstract: We report several new crab specimens, representing new taxa and new occurrences from the Miocene of Veracruz and Chiapas, SE Mexico. Most of the specimens were collected by the late Emily H. Vokes, in 1963 from outcrops of the Agueguexquite Formation, Veracruz, Mexico. The age range of the studied material support an upper Miocene age for the Agueguexquite Formation, as previously suggested. Ranina sp. and Portunus sp. cf. P. atecuicitlus Vega et al.1999 from the middle Miocene, Tuxpan Formation, are also reported. We also illustrate an incomplete portunoid specimen from the lower Miocene Tulijá Formation of Chiapas, similar to Necronectes A. Milne Edwards, 1881. The presence of Hepatus Latreille, 1802, Persephona Leach, 1817, and Euphylax Stimpson, 1862a, in the Agueguexquite Formation represent the first record of these genera in the fossil record of Mexico. The occurrence of Eupilumnus ? vokesae Luque, sp. nov. would represent the first fossil record of the genus known to date, extending its stratigraphic record into the Miocene. Eurytium granulosus Schweitzer, Velez-Juarbe, Martinez, Collmar-Hull, Feldmann and Santos, 2008, first reported from the Miocene of Puerto Rico is also identified among the specimens here studied. Highlights: Collection of decapod crustaceans collected 60 years ago is finally reported from Mexico. The age of the main fossiliferous lithostratigraphic unit (Agueguexquite Formation) is defined. Not many new taxa are reported but an affinity to the once called Miocene Gatunian Province, is confirmed. Finally, this report represents an important addition to the knowledge of the diverse crustacean fossil fauna from Mexico.